Endogenous quality and firm entry - Faustino, Rui (2019)
During economic expansions the net product creation and average product quality increase as firms introduce new products with higher quality. The introduction of new products with higher quality produces a quality bias in price level measures. In this paper I develop a firm-entry model with endogenous quality of consumer goods. Following a TFP shock, the price level increases not only due to a larger number of varieties but also due to a higher average quality. Simultaneously, the channel of endogenous quality acts as a propagation mechanism to other variables in the economy, amplifying their response to shocks. This channel can also be either contractionary or shut down, depending on how consumers derive utility from quality.